2013
DOI: 10.1002/pds.3408
|View full text |Cite
|
Sign up to set email alerts
|

Safety information in drug labeling: a comparison of the USA, the UK, and Japan

Abstract: Substantial differences in safety information exist depending upon outcome measures and therapeutic areas among the US, the UK, and the Japanese labels. This underscores the need for further analyses to determine causes of these differences to optimize drug safety regulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
26
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 22 publications
2
26
0
3
Order By: Relevance
“…). Shimazawa and Ikeda () and Kesselheim et al. () indicated that there were variances in the information provided in different countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…). Shimazawa and Ikeda () and Kesselheim et al. () indicated that there were variances in the information provided in different countries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biologicals and small molecule drugs are governed by different legislation (Nieminen et al 2005). Shimazawa and Ikeda (2013) and Kesselheim et al (2013) indicated that there were variances in the information provided in different countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has highlighted various types of inconsistencies in the reporting of drug safety information, including discrepancies among the reports for bio-equivalent drugs, or reports used in different countries [28-30]. However, systematic comparisons of the major safety data sets used in system pharmacological models and assessment of the impact of data-set choice on prediction performance are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Denileukin diftitox and tositumomab which were approved for lymphoma by the FDA in 1999 and 2003, respectively, remain unavailable in both the EU and Japan, probably because better treatment modalities are available. can affect regulatory decisions [5]. A previous study revealed substantial differences in the pharmacogenomic information included on labels from the USA, the UK and Japan [3].…”
mentioning
confidence: 98%